Oxygen and peroxide bridged uranyl(vi) dimers bearing tetradentate hybrid ligands: supramolecular self-assembly and generation pathway. Issue 18 (6th August 2020) - Liu, Jun; Wang, Xueyu; Chen, Baihua; Lv, Lina; Li, Qiang; Li, Xingliang; Ding, Songdong; Yang, Yanqiu
Abstract : Crystals of U(vi ) complexes with N, N, N ′, N ′-tetramethyl-2, 2′-bipyridine-6, 6′-dicarboxamide and N, N, N ′, N ′-tetramethyl-1, 10-phenanthroline-2, 9-dicarboxamide were obtained under variable reaction conditions, and the structures were determined by single-crystal X-ray diffraction. Abstract : Crystals of U(vi ) (UO2 2+ ) complexes with N, N, N ′, N ′-tetramethyl-2, 2′-bipyridine-6, 6′-dicarboxamide (TMBiPDA) and N, N, N ′, N ′-tetramethyl-1, 10-phenanthroline-2, 9-dicarboxamide (TMPhenDA) were isolated from different solutions under variable reaction conditions, and the structures were determined by single-crystal X-ray diffraction. All are dimeric complexes bridged by ligand atomic O and molecular O2, denoted as U–O–U′ and U–O2 –U′ tectons, respectively. The U–O–U′ dimer is composed of two pentagonal bipyramids of the UO2 2+ moiety sharing a bridging O-apex, while the U–O2 –U′ tecton is composed of two hexagonal bipyramids sharing a peroxo-edge. The two uranyl groups in both U–O–U′ and U–O2 –U′ tectons supported by TMBiPDA share one equatorial plane. However, bent U–O2 –U′ tectons supported by TMPhenDA have been observed in crystals isolated from different solvents. Dimeric complexes pack into crystal materials by abundant C–H⋯O interactions, between the C–H donors from amide methyls and aromatic rings of ligands and the O-acceptors from the perchlorates, uranyl groups, and peroxide bridge. Another non covalent interaction driving the supramolecular assembly is the π–π interactions between the parallel aromatic rings. Multiple techniques, including absorption spectrophotometry, Raman spectroscopy, and electro-spray ionization – mass spectrometry (ESI-MS), were utilized to understand the pathway to the formation of the uranyl dimers in solutions. Results indicate that the U–O–U′ or U–O2 –U′ tectons are yielded, through sequential redox reactions of the uranyl group, from the same precursor [UO2 L] 2+ and the peroxide ligand O2 2− that formed in situ . The nature of ligands as well as the reaction conditions, such as temperature, solvent, pH, and light, etc ., plays significant roles in the selection of the bridging ligands (O 2− or O2 2− ) in crystal materials.